The Formative Assessment Practice in Vocational High Schools: Case Study - Suryaningsih, Dewi; Priyana, Joko (PT FORMOSA CENDEKIA GLOBAL, 2024)
In Merdeka Curriculum, the application of formative assessment improves teaching and learning quality. This study aims to explore (1) the implementation of formative assessments techniques’ practices in vocational high schools, (2) challenges of the implementation of formative assessments in vocational high schools. This research is qualitative case study research that applies semi-structured interviews, classroom observations, and document studies. Data from this study were collected from a Center of Excellent (CoE) vocational high school in Gunungkidul area involving four English teachers and one school principal. The study found that schools applied various formative assessment techniques based on learning objectives. Teachers also found some challenges in implementation of formative assessments such as limited learning facilities, limited time allocation, and teachers’ willingness